Effect of NPK and Bacillus-coated NPK fertilizer on biomass, nutrient content in soil and nutrient uptake by lettuce - Hindersah, Reginawanti; Setiawati, Mieke Rochimi; Suryatmana, Pujawati; Fitriatin, Betty Natalie; Aditya, Fasa; Nugraha, Gita Bina; Risanti, Rara Rahmatika; Asmiran, Priyanka (Universitas Padjadjaran, 2023)
The Inoculation of beneficial soil microbes is an effective method for lowering doses of inorganic fertilizers. This study was aimed to observe and compare the effect of doses and formulas of Bacillus-coated NPK (BCN) and conventional NPK fertilizers on biomass, major macro-nutrient in soil and their uptake by shoots of lettuce (Lactuca sativa L.); as well as evaluate the potency of BCN for decreasing doses of NPK fertilizers. The greenhouse experiment was set up in a randomized block design with seven treatments and five replications. The treatments included one and a half doses of recommended NPK fertilizer and two BCN fertilizer formulas; control treatment was without any fertilizer. This experiment showed that NPK fertilizer had comparable effect with BCN on growth traits; but application of NPK and coated NPK had a potency to increase the fresh weight of lettuce up to 24-45% which was in line with the increase of shoot-to-roots ratio. The potassium (K) content in soil and their uptake in lettuce shoots depend on doses and type of NPK but Nitrogen (N) and Phosphorus (P) content in soil and in shoot were not determined by treatments. The results showed that the recommended NPK dose (200 kg/ha) for lettuce can be reduced up to 50%; moreover, 50% of BCN enabled to maintain the N, P and K uptake as well as the lettuce yield.